2001
DOI: 10.2166/wst.2001.0057
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous nitrification and denitrification in biofilters with real time aeration control

Abstract: The aim of this article is to present a new biological aerated filter (BAF) for nitrogen removal based on simultaneous nitrification and denitrification. Contrary to the systems which integrate both an aerated and a non-aerated zone to allow complete nitrogen removal in one compact or two different units (pre-denitrification and nitrification), this upflow BAF system is based on the principle of simultaneous nitrification and denitrification since the filter is completely aerated. The denitrification process i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Similarly, authors such as Punzava et al [25], who combined processes of nitrification and denitrification in the same biofilm reactor, observed that denitrification occurred in spite of the presence of oxygen.…”
Section: Nitrogen Removalmentioning
confidence: 81%
“…Similarly, authors such as Punzava et al [25], who combined processes of nitrification and denitrification in the same biofilm reactor, observed that denitrification occurred in spite of the presence of oxygen.…”
Section: Nitrogen Removalmentioning
confidence: 81%
“…Nevertheless, this phenomenon may occur due to a reduced efficiency of oxygen transfer provided by a high concentration of biomass and high viscosity of the medium. In this manner, the inner regions of the biological flocs possibly did not receive oxygen and became anoxic zones, thereby providing favorable conditions for denitrification (Puznava et al, 2000). Moreover, since sludge growth was high, part of the total nitrogen removal may result from a higher nutrient uptake.…”
Section: Evaluation Of the Hydraulic Retention Timementioning
confidence: 99%
“…In the wastewater treatment systems that use an attached biomass, the total balance of the nitrogen in the liquid phase is often not satisfied because anoxic conditions can occur in the deeper areas of the biofilm, allowing for the denitrification even if dissolved oxygen is still present in the liquid phase (Walters et al 2009;Okabe et al 1996;Satoh et al 2004). In addition, Pochana and Keller (1999) and Puznava et al (2001) show that the simultaneous nitrification and denitrification (SND) could occur as a consequence of the DO concentration gradients within microbial flocs or biofilms. Nitrifiers will develop on the surface of the biofilm where there are rather high DO levels, whereas denitrifiers will be present inside the biofilm due to the low levels or absence of oxygen.…”
Section: The Flux Modelmentioning
confidence: 99%